Ionic conductor ceramic material and preparation method thereof

Using Na2CO3, MgCO3, ZrO2, NH4H2PO4 and SiO2 as raw materials, and combining ball milling, pre-firing and sintering processes, the problems of insufficient conductivity and low purity of ion conductor ceramic materials were solved, and high-performance ion conductor ceramic materials were prepared.

CN119504259APending Publication Date: 2025-02-25CHANGCHUN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411676551.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing ionic conductor ceramic materials have insufficient ionic conductivity, and the sol-gel preparation process is complex, leaving a lot of residual organic matter, resulting in low material purity.

Method used

Ion conductor ceramic materials were prepared using Na2CO3, MgCO3, ZrO2, NH4H2PO4 and SiO2 as raw materials through mixing, first ball milling, pre-firing, second ball milling and sintering. Flux and sintering aids were used to improve particle bonding, and atmosphere and temperature were controlled to remove impurities, thereby improving purity and density.

Benefits of technology

This improved the ion conductivity and mechanical properties of ion-conducting ceramic materials, reduced the sintering temperature and time, and enhanced the stability and reliability of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504259A_ABST
    Figure CN119504259A_ABST
Patent Text Reader

Abstract

The invention relates to the field of ionic conductors, in particular to an ionic conductor ceramic material and a preparation method thereof, and the ionic conductor ceramic material comprises Na2CO3, MgCO3, Zr02, NH4H2P04 and Si O2. The preparation method comprises the following steps: mixing the Na2CO3, the MgCO3, the Zr02, the NH4H2P04 and the SiO2 to obtain a first mixture; adding a dispersing agent into the first mixture, and carrying out first ball milling to obtain a second mixture; pre-sintering the second mixture, and carrying out a preliminary reaction to obtain a pre-sintered second mixture; carrying out secondary ball milling on the pre-sintered second mixture to obtain a second mixture subjected to secondary ball milling; and sintering the second mixture after the second ball milling to obtain the ionic conductor ceramic material. According to the prepared ionic conductor ceramic material, the conductive efficiency is improved, and meanwhile, a high-purity material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ion conductor ceramic materials, and in particular to an ion conductor ceramic material and a preparation method thereof. Background Art

[0002] Ion conductor ceramic materials refer to ceramic materials in which ions inside the ceramic can migrate in the lattice or amorphous structure at a certain temperature, thereby producing ionic conductivity.

[0003] Entering the 21st century, with the rapid development of energy storage and conversion fields (such as solid-state batteries) and sensor technology, the demand for high-performance ion conductor ceramic materials has increased dramatically. This has prompted scientists to conduct more in-depth research on the ion conduction mechanism of materials and develop new ion conductor ceramic materials with higher ion conductivity, better chemical stability and mechanical properties to meet the requirements of practical applications. NASICON materials have the advantages of higher ion conductivity, better thermal stability and chemical stability, and have potential application value in the fields of solid-state batteries, sensors, etc.

[0004] Although great progress has been made in ion conductor ceramic materials, their ionic conductivity still needs to be further improved in many application scenarios. In addition, when preparing the raw materials by the sol-gel method, the concentration, pH value, reaction temperature, stirring speed, etc. of the solution need to be strictly controlled. Not only is the process complicated, but the reaction time is long and there is a lot of residual organic matter.

[0005] Therefore, it is of great practical significance to develop an ionic conductor ceramic material with high conductivity and high purity and a preparation method thereof. Summary of the invention

[0006] In view of this, the present invention provides an ion conductor ceramic material and a preparation method thereof, aiming to solve the problem that the conductivity of existing ion conductor ceramic materials is limited, and when the raw materials are prepared by a sol-gel method, the process is complicated and there is a lot of residual organic matter, resulting in low purity of the ceramic material.

[0007] In one aspect, the present invention provides an ion conductor ceramic material, which includes Na2C03, MgCO3, Zr02, NH4H2P04 and SiO2.

[0008] Furthermore, the mass ratio of Na2C03, MgCO3, Zr02, NH4H2P04 and SiO2 is 1:1:2:2:1.

[0009] On the other hand, the present invention also provides a method for preparing the ion conductor ceramic material, comprising:

[0010] Mixing Na2C03, MgCO3, Zr02, NH4H2PO4 and SiO2 to obtain a first mixture;

[0011] Adding a dispersant to the first mixture and performing a first ball milling to obtain a second mixture;

[0012] pre-calcining the second mixture to perform a preliminary reaction to obtain a pre-calcined second mixture;

[0013] ball-milling the pre-calcined second mixture for a second time to obtain a second ball-milled second mixture;

[0014] The second mixture after the second ball milling is sintered to obtain the ion conductor ceramic material.

[0015] Preferably, the first ball milling time is 22-24 hours, and further preferably, the first ball milling time is 24 hours.

[0016] Furthermore, a flux and a sintering aid are added to the pre-sintered second mixture before ball milling.

[0017] Furthermore, the amount of the flux is 5-10 parts, the amount of the sintering aid is 3-8 parts, the flux is one of lithium fluoride or sodium fluoride; and the sintering aid is titanium dioxide.

[0018] Preferably, the flux is 7 parts and the sintering aid is 6 parts.

[0019] Preferably, the flux is lithium fluoride.

[0020] Furthermore, the pre-burning is carried out in a protective atmosphere, and the gas flow rate is controlled at 20-30 mL / min.

[0021] Preferably, the protective atmosphere is nitrogen or argon.

[0022] Preferably, the gas flow rate is 30 mL / min.

[0023] Furthermore, the dispersant is anhydrous ethanol, which is used to dissolve the first mixture.

[0024] Furthermore, the sintering temperature is 1000-1200° C., and the sintering time is 11-13 hours.

[0025] Preferably, the sintering temperature is 1100° C. and the sintering time is 12 hours.

[0026] Furthermore, the pre-firing temperature is 700-900°C, the time is 4-8 hours, and the heating rate is 1-3°C / min.

[0027] Preferably, the pre-firing temperature is preferably 800° C., the pre-firing time is preferably 6 hours, and the heating rate is preferably 2° C. / min.

[0028] Furthermore, the temperature of the second ball milling is 20-25° C., and the time of the second ball milling is 23-24 hours.

[0029] Preferably, the temperature of the second ball milling is 23° C., and the time of the second ball milling is 24 hours.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. An ion conductor ceramic material of the present invention is doped with sodium ions and magnesium ions, and a more stable structure can be formed after the elements enter the lattice. This more stable structure can provide a more stable framework for the transmission of sodium ions, reduce the obstacles to ion transmission caused by structural changes, and thus improve the ion conduction performance to a certain extent. In addition, the structural stability of the material is improved, so that ions can migrate more smoothly in the lattice.

[0032] 2. The present invention adopts the solid phase sintering method, firstly mixes the raw materials and ball mills them, then pre-sinters them, then conducts secondary ball milling, and finally conducts sintering. During the sintering process, some impurities can be removed by volatilization, etc., thereby improving the purity of the ion conductor ceramic material. And the sintered ion conductor ceramic material has a higher density and strength, better mechanical properties, can withstand certain external forces and pressures, and has better stability and reliability in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0034] Figure 1 A flow chart for preparing an ion conductor ceramic material provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0035] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0036] Entering the 21st century, with the rapid development of energy storage and conversion fields (such as solid-state batteries) and sensor technology, the demand for high-performance ion conductor ceramic materials has increased dramatically. This has prompted scientists to study the ion conduction mechanism of materials more deeply and develop new ion conductor ceramic materials with higher ion conductivity, better chemical stability and mechanical properties to meet the requirements of practical applications. NAS I CON type materials have the advantages of higher ion conductivity, better thermal stability and chemical stability, and have potential application value in the fields of solid-state batteries, sensors, etc.

[0037] Although great progress has been made in ion conductor ceramic materials, their ionic conductivity still needs to be further improved in many application scenarios. In addition, when the raw materials are prepared by the traditional sol-gel method, the concentration, pH value, reaction temperature, stirring speed, etc. of the solution need to be strictly controlled. Not only is the process complicated, but the reaction time is long and there are many residual organic substances, which leads to the problem of low purity of ion conductor ceramic materials.

[0038] The invention provides an ion conductor ceramic material, comprising: Na2C03, MgCO3, Zr02, NH4H2P04 and SiO2.

[0039] In the present invention, the mass ratio of Na2C03, MgCO3, Zr02, NH4H2PO4 and SiO2 is 1:1:2:2:1.

[0040] It is understandable that doping with sodium and magnesium ions can form a more stable structure after the elements enter the lattice. This more stable structure can provide a more stable framework for the transmission of sodium ions, reduce the obstacles to ion transmission caused by structural changes, and thus improve the ion conductivity to a certain extent. The improved structural stability of the material allows ions to migrate more smoothly in the lattice, enhances the mechanical properties of ion conductor ceramic materials, and thus reduces the sintering temperature and increases the sintering rate.

[0041] See also Figure 1 As shown, a method for preparing an ion conductor ceramic material provided by an embodiment of the present invention comprises:

[0042] Mixing Na2C03, MgCO3, Zr02, NH4H2PO4 and SiO2 to obtain a first mixture;

[0043] Adding a dispersant to the first mixture, and performing a first ball milling to obtain a second mixture;

[0044] pre-calcining the second mixture to perform a preliminary reaction to obtain a pre-calcined second mixture;

[0045] ball-milling the pre-calcined second mixture for a second time to obtain a second ball-milled second mixture;

[0046] The second mixture after the second ball milling is sintered to obtain the ion conductor ceramic material.

[0047] Specifically, the Na2C03, MgCO3, Zr02, NH4H2P04 and SiO2 are all ultrafine powders with a purity greater than 99%.

[0048] Specifically, the first ball milling time is 22-24 hours, and more preferably, the first ball milling time is 24 hours.

[0049] Specifically, the secondary ball milling time 9 is preferably 24 hours.

[0050] Specifically, the sintered second mixture is taken out and put into a mortar, and ground into fine powder to obtain ion conductor ceramic material powder.

[0051] Specifically, the first mixture is placed in a ball mill, an appropriate amount of dispersant is added, and then a first ball milling process is performed so that the first mixture can be fully dissolved and mixed to obtain a second mixture. The second mixture is placed in an alumina crucible and pre-burned in a muffle furnace to make the second mixture react initially; the pre-burned second mixture is taken out and placed in a ball mill, and ball milled again to make the second mixture more uniform; the second mixture after the second ball milling is placed in an alumina crucible and sintered in a muffle furnace to make the second mixture fully react. Finally, the sintered second mixture is taken out and ground to obtain an ion conductor ceramic material powder.

[0052] It can be understood that the method of mixing the raw materials, ball milling, pre-burning, then ball milling for the second time, and finally sintering allows the raw materials to be evenly mixed at the molecular level, thereby ensuring the consistency of the composition. The process of this method is simple. During the sintering process, some impurities can be removed by volatilization, etc., ensuring the uniform doping of sodium ions and magnesium ions, which not only improves the ionic conductivity, but also improves the purity of the ion conductor ceramic material. The doping of magnesium ions improves the density and strength of the ion conductor ceramic material, effectively reduces the temperature and time required for sintering, and enhances the mechanical properties of the ion conductor ceramic material, so that it can withstand certain external forces and pressures, and has better stability and reliability in practical applications.

[0053] In the present invention, flux and sintering aid are added to the pre-sintered second mixture before ball milling.

[0054] In the present invention, the amount of flux is 5-10 parts, the amount of sintering aid is 3-8 parts, the flux is one of lithium fluoride or sodium fluoride; the sintering aid is titanium dioxide.

[0055] It is understandable that the added flux accounts for 5%-10% of the total mass of the raw materials, and the sintering aid accounts for 3%-8% of the total mass of the raw materials.

[0056] Specifically, the added flux is preferably 7 parts, and the sintering aid is preferably 6 parts; the flux is preferably lithium fluoride.

[0057] It is understandable that adding flux and sintering aid to the second mixture before secondary ball milling improves the bonding condition between the raw material particles, the particles are tightly bonded together, the porosity of the material is reduced, the density is increased, and the excessive volatilization of sodium ions at high temperatures is effectively prevented, the stability of the chemical composition of the ion conductor ceramic material is maintained, and the preparation process of the ion conductor ceramic material is smoother. In addition, the flux and sintering aid help improve the ion lattice structure, accelerate the diffusion process of ions, and improve the ion conductivity, so that the sintering process can be completed at a lower temperature, thereby reducing the sintering temperature and time and increasing the sintering rate.

[0058] In the present invention, the pre-calcination is carried out in a protective atmosphere, and the gas flow rate is controlled at 20-30 mL / min.

[0059] Specifically, the protective atmosphere is nitrogen or argon.

[0060] It is understandable that the addition of nitrogen or argon can effectively isolate oxygen and prevent oxidation reactions of some metal ions in the raw materials, thereby improving the purity of the ion conductor material.

[0061] Specifically, the gas flow rate is preferably 30 mL / min.

[0062] It is understandable that the flow rate of the atmosphere needs to be properly controlled to avoid excessive gas flow causing temperature fluctuations in the furnace or blowing away the raw materials. The specific flow rate should be adjusted according to the size of the pre-burning equipment and the amount of samples.

[0063] In the present invention, the dispersant is anhydrous ethanol, which is used to dissolve the first mixture.

[0064] In the present invention, the sintering temperature is 1000-1200° C. and the sintering time is 11-13 hours.

[0065] Specifically, the sintering temperature is preferably 1100° C., and the sintering time is preferably 12 hours.

[0066] In the present invention, the pre-calcination temperature is 700-900° C., the time is 4-8 hours, and the heating rate is 1-3° C. / min.

[0067] Specifically, the calcination temperature is preferably 800° C., the calcination time is preferably 6 hours, and the heating rate is preferably 2° C. / min.

[0068] It is understandable that the pre-burning temperature is between 700-900℃, which is determined based on the reaction characteristics of the material. When the temperature is lower than 700℃, the reaction rate between the raw materials is too slow, which may lead to incomplete reaction and generate more intermediate products; and the temperature is higher than 900℃, which may cause excessive volatilization or local overheating of the raw materials, resulting in uneven composition and affecting the quality of the final product. The pre-burning time is between 4-8 hours. This time range allows the raw materials to fully react and form a relatively stable precursor structure. Slow heating can allow the raw materials to have enough time to fully contact and react. If the heating rate is too fast, the temperature gradient inside the material will be large, and the thermal stress generated may cause the material to have microstructural damage during the pre-burning process, thereby affecting its ion conduction and other properties.

[0069] In the present invention, the temperature of the second ball milling is 20-25° C., and the time of the second ball milling is 23-24 hours.

[0070] Specifically, the temperature of the second ball milling is preferably 23° C., and the time of the second ball milling is preferably 24 hours.

[0071] Example 1

[0072] 1. Mix 10 g Na2C03, 10 g MgCO3, 20 g Zr02, 20 g NH4H2PO4 and 10 g SiO2 to obtain a first mixture;

[0073] 2. Put the first mixture into a ball mill, add appropriate amounts of anhydrous ethanol and nitrogen, control the gas flow rate of nitrogen at 30 mL / min, and then perform the first ball milling treatment for 24 hours to fully dissolve the first mixture and mix uniformly to obtain the second mixture;

[0074] 3. The second mixture was placed in an alumina crucible and pre-fired in a muffle furnace to allow the second mixture to initially react. The pre-fired temperature was 800° C., the pre-fired time was 6 hours, and the heating rate was 2° C. / min.

[0075] 4. The second mixture after pre-calcination was taken out and put into a ball mill, and then 4.9 g of lithium fluoride and 4.2 g of titanium dioxide were added, and a second ball milling was performed for 24 hours.

[0076] 5. Put the second mixture after the second ball milling into an alumina crucible and sinter it in a muffle furnace to make the second mixture fully react. The sintering temperature is 1100°C and the sintering time is 12 hours. Take out the sintered second mixture, put it into a mortar, and grind it into fine powder to obtain ion conductor ceramic material powder.

[0077] Example 2

[0078] 1. Mix 15 parts of Na2CO3, 15 parts of MgCO3, 30 parts of ZrO2, 30 parts of NH4H2PO4 and 15 parts of SiO2 to obtain a first mixture;

[0079] 2. Put the first mixture into a ball mill, add appropriate amounts of anhydrous ethanol and nitrogen, control the gas flow rate of nitrogen at 30 mL / min, and then perform the first ball milling treatment for 24 hours to fully dissolve the first mixture and mix uniformly to obtain the second mixture;

[0080] 3. The second mixture was placed in an alumina crucible and pre-fired in a muffle furnace to allow the second mixture to initially react. The pre-fired temperature was 800° C., the pre-fired time was 6 hours, and the heating rate was 2° C. / min.

[0081] 4. The second mixture after pre-calcination was taken out and put into a ball mill, and then 7.35 g of lithium fluoride and 6.3 g of titanium dioxide were added and ball milled for a second time for 24 hours.

[0082] 5. Put the second mixture after the second ball milling into an alumina crucible and sinter it in a muffle furnace to make the second mixture fully react. The sintering temperature is 1100°C and the sintering time is 12 hours. Take out the sintered second mixture, put it into a mortar, and grind it into fine powder to obtain ion conductor ceramic material powder.

[0083] Example 3

[0084] 1. Mix 20 g Na2CO3, 20 g MgCO3, 40 g ZrO2, 40 g NH4H2PO4 and 20 g SiO2 to obtain a first mixture;

[0085] 2. Put the first mixture into a ball mill, add appropriate amounts of anhydrous ethanol and nitrogen, control the gas flow rate of nitrogen at 30 mL / min, and then perform the first ball milling treatment for 24 hours to fully dissolve the first mixture and mix uniformly to obtain the second mixture;

[0086] 3. The second mixture was placed in an alumina crucible and pre-fired in a muffle furnace to allow the second mixture to initially react. The pre-fired temperature was 800° C., the pre-fired time was 6 hours, and the heating rate was 2° C. / min.

[0087] 4. The second mixture after pre-calcination was taken out and put into a ball mill, and then 9.8 g of lithium fluoride and 8.4 g of titanium dioxide were added for secondary ball milling for 24 hours.

[0088] 5. Put the second mixture after the second ball milling into an alumina crucible and sinter it in a muffle furnace to make the second mixture fully react. The sintering temperature is 1100°C and the sintering time is 12 hours. Take out the sintered second mixture, put it into a mortar, and grind it into fine powder to obtain ion conductor ceramic material powder.

[0089] Example 4

[0090] 1. Mix 30 g Na2CO3, 30 g MgCO3, 60 g ZrO2, 60 g NH4H2PO4 and 30 g SiO2 to obtain a first mixture;

[0091] 2. Put the first mixture into a ball mill, add appropriate amounts of anhydrous ethanol and nitrogen, control the gas flow rate of nitrogen at 30 mL / min, and then perform the first ball milling treatment for 24 hours to fully dissolve the first mixture and mix uniformly to obtain the second mixture;

[0092] 3. The second mixture was placed in an alumina crucible and pre-fired in a muffle furnace to allow the second mixture to initially react. The pre-fired temperature was 800° C., the pre-fired time was 6 hours, and the heating rate was 2° C. / min.

[0093] 4. The second mixture after pre-calcination was taken out and put into a ball mill, and then 14.7 g of lithium fluoride and 12.6 g of titanium dioxide were added and ball milled for a second time for 24 hours.

[0094] 5. Put the second mixture after the second ball milling into an alumina crucible and sinter it in a muffle furnace to make the second mixture fully react. The sintering temperature is 1100°C and the sintering time is 12 hours. Take out the sintered second mixture, put it into a mortar, and grind it into fine powder to obtain ion conductor ceramic material powder.

[0095] Those skilled in the art will appreciate that the embodiments of the present application may be provided as methods, systems or computer program products. Therefore, the present application may adopt the form of a complete hardware embodiment, a complete software embodiment, or an embodiment in combination with software and hardware. Moreover, the present application may adopt the form of a computer program product implemented on one or more computer-usable storage media (including but not limited to disk storage, CD-ROM, optical storage, etc.) containing computer-usable program codes.

[0096] The present application is described with reference to flowcharts and / or block diagrams of methods, devices (systems) and computer program products according to embodiments of the present application. It should be understood that each process and / or box in the flowchart and / or block diagram, as well as the combination of processes and / or boxes in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor or other programmable data processing device to generate a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.

[0097] These computer program instructions may also be stored in a computer-readable memory capable of directing a computer or other programmable data processing device to operate in a specific manner, so that the instructions stored in the computer-readable memory produce an article of manufacture comprising an instruction device, which implements the process Figure 1 A process or multiple processes and / or boxes Figure 1 A function specified in one or more boxes.

[0098] These computer program instructions can also be loaded onto a computer or other programmable data processing device so that a series of operating steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby providing instructions for implementing the process in the computer or other programmable device. Figure 1 A process or multiple processes and / or boxes Figure 1 The steps for the functions specified in one or more boxes.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. An ion conductor ceramic material, characterized in that: Including Na2C03, MgCO3, Zr02, NH4H2P04 and SiO2.

2. The ion conductor ceramic material according to claim 1, characterized in that: The mass ratio of Na2C03, MgCO3, Zr02, NH4H2P04 and SiO2 is 1:1:2:2:

1.

3. A method for preparing an ion conductor ceramic material, characterized in that: include: Mixing Na2C03, MgCO3, Zr02, NH4H2P04 and SiO2 to obtain a first mixture; Adding a dispersant to the first mixture and performing a first ball milling to obtain a second mixture; pre-calcining the second mixture to perform a preliminary reaction to obtain a pre-calcined second mixture; ball-milling the pre-calcined second mixture for a second time to obtain a second ball-milled second mixture; The second mixture after the second ball milling is sintered to obtain the ion conductor ceramic material.

4. The method for preparing an ion conductor ceramic material according to claim 3, characterized in that: Flux and sintering aid are added before ball milling the pre-fired second mixture.

5. The method for preparing an ion conductor ceramic material according to claim 4, characterized in that: The amount of the flux is 5-10 parts, the amount of the sintering aid is 3-8 parts, the flux is one of lithium fluoride and sodium fluoride; the sintering aid is titanium dioxide.

6. The method for preparing an ion conductor ceramic material according to claim 3, characterized in that: The pre-burning is carried out in a protective atmosphere, and the gas flow rate is controlled at 20-30 mL / min.

7. The method for preparing an ion conductor ceramic material according to claim 3, characterized in that: The dispersant is anhydrous ethanol.

8. The method for preparing an ion conductor ceramic material according to claim 3, characterized in that: The sintering temperature is 1000-1200° C. and the sintering time is 11-13 hours.

9. The method for preparing an ion conductor ceramic material according to claim 3, characterized in that: The pre-firing temperature is 700-900° C., the time is 4-8 hours, and the heating rate is 1-3° C. / min.

10. The method for preparing an ion conductor ceramic material according to claim 3, characterized in that: The temperature of the second ball milling is 20-25° C., and the time of the second ball milling is 23-24 hours.